Transfusion Medium with Cryopreserved Umbilical Blood Nucleated Cells: From Procurement to Possible Clinical Usage - Perekhrestenko, P. M.; Glukhenkaya, G. T.; Kalinichenko, T. A.; Algazinova, M. K. (Problems of Cryobiology and Cryomedicine, 2005)
There is characterised the transfusion medium with cryopreserved umbilical blood nucleated cells as hemocomponent therapy means according to strictly differentiated indications in patients with hemodepressive states in oncological and oncohematological clinics.